Low loading Pt on TiO2 for the ultra‐selective hydrogenation of chloronitrobenzenes to chloroanilines. Issue 6 (6th February 2023) - Duan, Mingyu; He, Daiping; Ding, Yufang; Sun, Junli; Jiang, Ping; Zhou, Gongbing
Abstract: Low loading Pton TiO2 were prepared by an impregnation‐reduction process for chemoselective hydrogenation of chloronitrobenzenes (CNBs) to chloroanilines (CANs). The structure and physicochemical properties were characterized by N2 adsorption‐desorption, X‐ray diffraction, high resolution transmission electron microscopy, X‐ray photoelectron spectroscopy and temperature programmedreduction. The low loading Pt(≤0.08 wt %) on TiO2 exhibited outstanding chemoselectivity for the catalytic hydrogenation of CNBs to CANs, without any disturbance on carbon‐chlorine bond. The characterization data suggested that the Pt particles were highly dispersed on TiO2 and strongelectronicinteractionsoccur between the dispersedPt andTiO2 support, which led toelectron deficiency of nearly all Pt and production of suboxide TiOx species (x<2) in the 0.08 wt % Pt/TiO2 . The electron‐deficient Pt and suboxide TiOx species favor N=O bondactivation, leading to its unique chemoselectivity. Abstract : Low loading Pt (<0.08 wt %) onTiO2 support is found to be an efficient approach to improve the catalytic selectivity of Pt (100 %) for the hydrogenation of chloronitrobenzenes to chloroanilines, without any effect on carbon‐chlorine bond.